Maltodextrin fast dissolving films for quercetin nanocrystal delivery. A feasibility study. (5th May 2015) - Lai, Francesco; Franceschini, Ilaria; Corrias, Francesco; Sala, Maria Chiara; Cilurzo, Francesco; Sinico, Chiara; Pini, Elena
Highlights: Quercetin nanosuspensions were prepared by high pressure homogenization. Maltodextrin fast dissolving films were loaded with quercetin nanocrystals. The loading of nanocrystals into the film did not affect its elasticity and ductility. Dissolution rate of film loaded nanocrystals was much higher than that of bulk drug. Abstract: The objective of this study was to evaluate the feasibility to prepare fast dissolving films as quercetin nanocrystal delivery systems, using maltodextrins as film forming material and glycerin as plasticizer, with the goal of enhancing quercetin oral bioavailability. Quercetin nanosuspensions were prepared using a high-pressure homogenizer, and then directly used to prepare the films by a casting method. Spectroscopic and calorimetric analysis evidenced that reduction of quercetin size at nanoscale and incorporation in maltodextrin films do not affect the solid state of the active ingredient. The loading of quercetin nanocrystals into the film determined a slight variation of film elasticity and ductility. Indeed, the elastic modulus of the loaded films resulted about a half of the placebo ones, while the elongation at break increased four folds. Free and film loaded quercetin nanocrystals showed a comparable dissolution rate, much higher than that of bulk quercetin.